The crystal structure of (1-(pyridin-2-yl)-N-(pyridin-2-ylmethyl)-N-((1-(4-vinylbenzyl)-1H-benzo[d]imidazol-2-yl)methyl)methanamine-κ 4 N,N′,N″,N‴)tris(nitrato-kO,O′)-erbium(III), C29H27ErN8O9 - Wang Hai-Ping; Chen Lu; Liang Jia-Jun; Huang Guo-Peng (Zeitschrift für Kristallographie - New Crystal Structures)
C29H27ErN8O9, triclinic, P1‾ $P\overline{1}$ (no. 2), a = 8.6681(2) Å, b = 13.0695(3) Å, c = 14.1408(4) Å, α = 80.130(2)°, β = 86.409(2)°, γ = 75.761(2)°, V = 1529.43(4) Å3, Z = 2, R gt(F) = 0.0382, wR ref(F 2) = 0.1110, T = 295 K.